Pengembangan Sistem Evaluasi Pembelajaran Akhlak Anak Usia Dini di Pondok Pesantren Salafiyah Nurhidayah Desa Bencah Kelubi - Erlina Rosni Putriadi Harahap; Zubaidah Amir MZ (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2026)
This study aims to analyze and develop a learning evaluation system for early childhood moral (akhlaq) education at Pondok Pesantren Salafiyah Nurhidayah, Riau. The research subjects consisted of the kiai, ustadz, and ustazah, while the research object was the evaluation system and moral assessment instruments for early childhood students (santri). A descriptive qualitative approach was employed, with data collection techniques comprising participatory observation, in-depth interviews, and documentation of non-test instruments. Data analysis techniques applied the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The research findings concluded that the learning evaluation system for early childhood moral education in this Islamic boarding school was developed through three main mechanisms that address two research questions: 1) The evaluation system is applied in an integrated manner through the division of conceptual evaluative roles by the kiai (macro-spiritual evaluation), ustadz (evaluation of cognitive manners and discipline), and ustazah (evaluation of affect and social interaction); 2) Instrument development is carried out through a non-test authentic assessment model that integrates daily anecdotal records, rubrics for performance assessment of manners, and participatory observation sheets of students' emotional development. The synergy of this system produces a valid, comprehensive, and sustainable child character development assessment model that aligns with early childhood psychology within the salaf pesantren ecosystem